2018
DOI: 10.1002/rcm.8265
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polyatomic primary ion chemistry on matrix effects in secondary ion mass spectrometry analysis

Abstract: Compared with C and Ar , water-containing cluster projectiles enhanced the sensitivity of TOF-SIMS determination of the chosen analytes and reduced the effect of signal suppression/enhancement in multicomponent samples and in different sample matrices. One possible explanation for this is that the (H O) projectile initiates on impact a nanoscale matrix environment that is very similar to that in frozen-hydrated samples in terms of the resulting ionisation effects. The competition between analytes for protons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…More than half of compounds, detected in the frozen hydrated state, are not detectable above the noise in the freeze-dried sample (compounds denoted with an asterisk in Supplementary Table 2). Water has a low gas phase basicity (665 kJ/mol) and acts as a matrix facilitating proton transfer for ionization. Water can also stabilize and trap both the cation and anion to reduce the ion suppression by salts . Furthermore, we found that polar molecules (low Log P ) are, generally, more strongly enhanced.…”
Section: Resultsmentioning
confidence: 77%
“…More than half of compounds, detected in the frozen hydrated state, are not detectable above the noise in the freeze-dried sample (compounds denoted with an asterisk in Supplementary Table 2). Water has a low gas phase basicity (665 kJ/mol) and acts as a matrix facilitating proton transfer for ionization. Water can also stabilize and trap both the cation and anion to reduce the ion suppression by salts . Furthermore, we found that polar molecules (low Log P ) are, generally, more strongly enhanced.…”
Section: Resultsmentioning
confidence: 77%
“…On this basis, it is suggested that in the impact site some type of concerted mechanism occurs between the energized water cluster and the analyte molecules to enhance the protonation process. It seems that close to an aqueous environment is created in the emission zone, and this idea has been supported by recent studies showing that the yield using water beams is very similar to the yield using argon cluster beams from analyte in a frozen hydrated matrix …”
mentioning
confidence: 76%
“…It seems that close to an aqueous environment is created in the emission zone, and this idea has been supported by recent studies showing that the yield using water beams is very similar to the yield using argon cluster beams from analyte in a frozen hydrated matrix. 39 These studies suggested that using the water cluster beam may have enhanced the ionization probability of the molecules studied to 10 −2 or above, a very encouraging result. A subsequent study applied 20 keV water cluster beams (H 2 O) n and what was termed "wet" argon cluster beams (an argon cluster beam dosed with water at a partial pressure just below 1 bar) to imaging a mouse brain tissue.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In secondary-ion mass spectrometry (SIMS), , the formation of molecular ions is a rather complex process and a complete theoretical understanding seems to still be missing . The formation and detection of large organic and biological molecules in SIMS was greatly improved by the use of gas-cluster ions as projectiles. Under such irradiation conditions, intact molecular ions were found to be sputtered from the specimens’ surface, while the number of emitted fragment species was reduced substantially. Still, ion yields were found to be typically very low. In sputtering, organic (positive) molecular ions emerge frequently as protonated species, [M + H] + , or cationized via the attachment of (alkali) metal ions, X, to the originally neutral molecule, [M + X] + . ,, Quite often, this approach led to enhanced SIMS ion yields or to the ability to detect molecular species from an organic substance at all. While beneficial for many analyses, the processes leading to cationization have not been investigated for gas cluster ion beams.…”
mentioning
confidence: 99%